International encyclopedia of government and politics - Magill, Frank N. (Frank Northen) 1907-1997; Bessette, Joseph M.; Gold, Derek (Toppan, 1996)
The International Encyclopedia of Government and Politics examines the full scope of the science and practice of politics. From the early political models of Aristotle and Plato to our own parliamentary system and questions of accountability and representation, 5000 years of government and politics are presented in some 350 authoritative entries. The encyclopedia covers thirteen major fields: Civil Rights and Liberties; Comparative Government; Economic Issues; Functions of Government; History of Government and Politics; International Government and Politics; Law and Jurisprudence; Local and Regional Government; Military; Political Philosophy; Politics (General); Religion and Government; and Types of Government. Each six-page entry introduces the reader to a topic in political science, explains the vocabulary, context, and significance of that topic, and includes a signed essay with an annotated bibliography written by an authority in the field. To help the reader in finding information, the main text of each essay is divided into three sections: Overview, Applications, and Context. The International Encyclopedia of Government and Politics has a comprehensive glossary and is fully indexed.